2020
DOI: 10.1159/000505532
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated Carcinomatosis of the Bone Marrow from Occult Breast Cancer Responding to a Sequence of Endocrine Therapy

Abstract: Patients with cancer of unknown primary (CUP) are generally treated with chemotherapy. Bone marrow involvement suggests an advanced stage, and CUP with disseminated carcinomatosis of the bone marrow (DCBM) appears to have a dismal prognosis. However, our case of CUP with DCBM was successfully treated with a sequence of endocrine therapy over a long period. A woman presenting with low back pain was found to have multiple bone metastasis without an identifiable primary tumor on imaging studies. Blood tests revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 14 publications
0
8
1
Order By: Relevance
“…Yamaguchi et al achieved response with palbociclib plus fulvestrant therapy in a patient with breast cancer with bone marrow metastases. (5) Although bicytopenia was present in our case report, we observed that dose…”
Section: Discussioncontrasting
confidence: 49%
“…Yamaguchi et al achieved response with palbociclib plus fulvestrant therapy in a patient with breast cancer with bone marrow metastases. (5) Although bicytopenia was present in our case report, we observed that dose…”
Section: Discussioncontrasting
confidence: 49%
“…In contrast, ET, although less rapid than chemotherapy in obtaining a disease response, is better tolerated and has no hematological toxicity. Therefore, endocrine agents, from the point of view of toxicity, can be used safely in the treatment of BC with DCBM (34).…”
Section: Discussionmentioning
confidence: 99%
“…The patient was treated initially with letrozole and then with a combination of fulvestrant and palbociclib as second-line treatment, resulting in a response to treatment lasting more than 1 year. Palbociclib was initiated at a reduced dose (75 mg/day), being concerned about a possible exacerbation of pre-existing hematological toxicity (34).…”
Section: Discussionmentioning
confidence: 99%
“…Garufi et al [ 5 ] reported a case of a Stage IV BMC patient with Hb 7.5 g/dL and Plt 110,000/μL who achieved CR with a combination of CDK4/6 inhibitors and aromatase inhibitors as first-line endocrine therapy and continued treatment for 26 months. Yamaguchi et al [ 6 ] started letrozole monotherapy for 2 years for BMC in latent breast cancer, and pancytopenia improved. The patient was then treated with a combination of a CDK4/6 inhibitor and fulvestrant for second-line therapy [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yamaguchi et al [ 6 ] started letrozole monotherapy for 2 years for BMC in latent breast cancer, and pancytopenia improved. The patient was then treated with a combination of a CDK4/6 inhibitor and fulvestrant for second-line therapy [ 6 ]. The present case had a similar course.…”
Section: Discussionmentioning
confidence: 99%